Chlamydomonas ATX1 is essential for Cu distribution to multiple cupro‐enzymes and maintenance of biomass in conditions demanding cupro‐enzyme‐dependent metabolic pathways. (3rd February 2022) - Pham, Keegan L. J.; Schmollinger, Stefan; Merchant, Sabeeha S.; Strenkert, Daniela
Abstract: Copper (Cu) chaperones, of which yeast ATX1 is a prototype, are small proteins with a Cu(I) binding MxCxxC motif and are responsible for directing intracellular Cu toward specific client protein targets that use Cu as a cofactor. The Chlamydomonas reinhardtii ATX1 (CrATX1) was identified by its high sequence similarity with yeast ATX1. Like the yeast homologue, CrATX1 accumulates in iron‐deficient cells (but is not impacted by other metal‐deficiencies). N‐ and C‐terminally YFP‐ATX1 fusion proteins are distributed in the cytoplasm. Reverse genetic analysis using artificial microRNA (amiRNA) to generate lines with reduced CrATX1 abundance and CRISPR/Cpf1 to generate atx1 knockout lines validated a function for ATX1 in iron‐poor cells, again reminiscent of yeast ATX1, most likely because of an impact on metalation of the multicopper oxidase FOX1, which is an important component in high‐affinity iron uptake. We further identify other candidate ATX1 targets owing to reduced growth of atx1 mutant lines on guanine as a sole nitrogen source, which we attribute to loss of function of UOX1, encoding a urate oxidase, a cupro‐enzyme involved in guanine assimilation. An impact of ATX1 on Cu distribution in atx1 mutants is strikingly evident by a reduced amount of intracellular Cu in all conditions probed in this work.